APPLYING MODERN TECHNOLOGY TO SERVE THE HOLY BOOK OF ALLAH: AYAT APPLICATION AND DAR AL ISLAM WEBSITES AS A MODEL - Noura abdulaziz mohamed al-ali (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
To improve the readership and understanding of the Holy Quran at a global level, it is vital to disseminate it to both Arab and non-Arab speakers with a wide range of facilities. Allah has bestowed some of his chosen believers, whom he favored disseminating the Holy Quran, to reach the horizons of readership of the Quran through websites. In the modern era, modern technology has been used and applied to serve the Holy Quran. This research aims at presenting a model of two websites that have contributed significantly to the service of disseminating the Quran and to the teaching to non-Arabic speakers. These efforts increase the benefit of the user and have accelerated more listening to the Holy Quran all over the world. It has also benefited the scientific and technical efforts to serve the Holy Quran everywhere in the world to bridge the gap between Arab and non-Arabic speakers for a better understanding of the Holy Book. The websites have helped the millions of non-Arabic speakers to read the Quran and encouraging more listening, worshiping, memorizing, learning, and studying the Quran by providing an accessible interpretation in different languages. The Islamic websites also conducted a set of courses to address the teaching of the Arabic language to non-native speakers as well. It also helps to improve the skill of searching on websites that ease the dissemination of the Holy Quran for non-Arabic speakers.